Transient ocular hypertension remodels astrocytes through S100B. - Weiran Huang; Kenji Matsushita; Rumi Kawashima; Susumu Hara; Yuichi Yasukura; Kaito Yamaguchi; Shinichi Usui; Koichi Baba; Andrew J Quantock; Kohji Nishida (PLoS ONE)
Glaucoma is a series of irreversible and progressive optic nerve degenerations, often accompanied by astrocyte remodeling as the disease progresses, a process that is insufficiently understood. Here, we investigated the morphology of retinal and optic nerve head (ONH) astrocytes under mechanical stress, and explored whether a specific phase is present that precedes astrocyte remodeling. A mouse model of transient ocular hypertension (OHT) and an in vitro cell stretch model were established to mimic the pathological conditions of increased intraocular pressure and mechanical stress on cultured cells. Glial fibrillary acidic protein (GFAP), S100B, and actin staining were used to characterize astrocyte morphology and cytoskeleton, with qPCR used to measure mRNA expression. We also silenced S100B expression and conduct RNA sequencing on ONH astrocytes. Astrocytes displayed weaker GFAP intensity (p < 0.0001) in the early-stage OHT mouse model, prior to the onset of hypertrophy, which was accompanied by an increase in GFAP mRNA expression (p < 0.0001) and a decrease in S100B mRNA expression (p < 0.001). In vitro-stretched astrocytes tended to contract and had fewer cellular processes and more elongated cell bodies. Downregulation of S100B expression occurred in in both the in vivo (p = 0.0001) and in vitro (p = 0.0023) models. S100B-silenced ONH astrocytes were similarly characterized by a slender morphology. In the RNA-seq analysis, genes downregulated by more than fivefold were predominantly enriched in terms related to nutrient metabolism, motor proteins and morphogenesis. Meanwhile, genes upregulated by more than fivefold were primarily associated with terms related to histone modification and visual perception. As an early response to mechanical stress, S100B expression is downregulated in astrocytes, which assume a slender morphology, reminiscent of cell "weakening." Silencing intracellular S100B expression induced similar morphology changes and altered the transcriptome. Stress-induced changes were reversible, with evidence of enhanced late-stage reactivation that is likely related to S100B.